2023
DOI: 10.1098/rspb.2023.0216
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition increases sperm production and quality inCataglyphisdesert ants

Abstract: Sperm competition is a pervasive evolutionary force that shapes sperm traits to maximize fertilization success. Indeed, it has been shown to increase sperm production in both vertebrates and invertebrates. However, sperm production is energetically costly, which may result in trade-offs among sperm traits. In eusocial hymenopterans, such as ants, mating dynamics impose unique selective pressures on ejaculate. Males are sperm limited: they enter adulthood with a fixed amount of sperm that will not be renewed. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…In Cataglyphis, AG size and sperm production are positively associated with sperm competition intensity which suggests that seminal fluid boosts sperm function (Ramm, 2020). In the same vein, it has been shown that sperm competition selects for increased sperm quality in Cataglyphis: in species with highly polyandrous females, males produce more viable sperm with lower levels of DNA fragmentation (Degueldre and Aron, 2023). Seminal fluid could help maintain high levels of sperm quantity and quality by furnishing (i) antioxidant enzymes that limit oxidative stress (Weirich et al, 2002;Collins et al, 2006;Baer et al, 2009); (ii) substances that sustain sperm metabolism (Blum et al, 1962;Alumot et al, 1969); and (iii) antimicrobial and antifungal enzymes (Baer et al, 2009;Peng et al, 2015;Cheŕasse et al, 2018;Davila et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Cataglyphis, AG size and sperm production are positively associated with sperm competition intensity which suggests that seminal fluid boosts sperm function (Ramm, 2020). In the same vein, it has been shown that sperm competition selects for increased sperm quality in Cataglyphis: in species with highly polyandrous females, males produce more viable sperm with lower levels of DNA fragmentation (Degueldre and Aron, 2023). Seminal fluid could help maintain high levels of sperm quantity and quality by furnishing (i) antioxidant enzymes that limit oxidative stress (Weirich et al, 2002;Collins et al, 2006;Baer et al, 2009); (ii) substances that sustain sperm metabolism (Blum et al, 1962;Alumot et al, 1969); and (iii) antimicrobial and antifungal enzymes (Baer et al, 2009;Peng et al, 2015;Cheŕasse et al, 2018;Davila et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Sperm production data for the nine study species were obtained from Degueldre and Aron (2023). Briefly, both accessory testes from each male were dissected in semen diluent.…”
Section: Sperm Productionmentioning
confidence: 99%
See 3 more Smart Citations